SISTEMA DE GESTÃO DA RESPONSABILIDADE SOCIAL CORPORATIVA: PROPOSTA PARA UMA ORGANIZAÇÃO MULTINACIONAL DA INDÚSTRIA AUTOMOBILÍSTICA BRASILEIRA - Araujo, Fernando Oliveira de (2005)
The complexity and scope of the social matter in Brazil has demanded from companies, as influential social entities, acute and effective actions oriented towards the narrowing of the social economic hiatus in their environment. Encouraged by this scenario, the development of investment criteria, mobilization programs, such as corporate volunteering, along with the corporate social responsibility management systems, have been targeting the joining of interests of the private investment to its sustainable and proactive social action.The current research, based on the case study of a multinational company from the Brazilian automobile industry, was initiated through a methodology strategy that took over the bibliographical review (in its state of art), the interviews with important players of the decision process, the social field investigations, as well as the feeling and professional experience the author has in relation with the theme. As a result of the scientific investigation, there is a proposal for the development of a corporate social management system, able to evaluate the effectiveness of corporate actions and their impact on the communities and supported social initiatives; to increase the value of the institutional image; to elevate the capacity to attract and retain talents.